Ninhos artificiais não substituem cavidades naturais para aves em remanescentes de vegetação nativa em matriz antropizada no sudeste do Brasil - Pedro, Mayara Kelly Do Prado (Universidade Federal de São Carlos, 2023)
Natural cavities in hollows are found in dry trunks, living trees and in the soil, being able to serve as shelter and reproduction places for several animals, including birds. With the advance of urbanization, these cavities have become scarcer, directly affecting the reproductive dynamics of birds that depend on this resource. In this way, the introduction of artificial nests could be a possible alternative to replace natural cavities in hollow ones and, thus, mitigate the effect of their scarcity. In this work, we evaluated the successful occupation by birds of 84 artificial nests made from dry cashew fruit (Lagenaria siceraria) and wooden boxes, installed in two remaining areas of native vegetation in the city of Sorocaba, SP. The nesting rate by birds was 3.57% (n=3) in the two monitored areas, with only the wren (Troglodytes musculus) nesting. Explanations why the results obtained in this work were not very expressive consist of the pre-existence of environmental filters due to the growing anthropic effect; in the installation of artificial nests in small and medium-sized trees; and the possible microclimate inside the nests.
Artificial nests do not replace natural cavities for birds in remnants of native vegetation in an anthropized matrix in southeastern Brazil
Keywords: Ninhos Artificiais; Nidificação; Reprodução de Aves; Artificial Nests; Nesting; Bird's Reproduction; CIENCIAS BIOLOGICAS::ECOLOGIA